Pengaruh Pembelajaran PAI BP Berbasis Teknologi Informasi Dan Komunikasi Terhadap Efektivitas Belajar Siswa - Tina Nurohmah; Aji , Aji Setiaji (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
This research is based on the problem of low student learning effectiveness and PAI and Ethics learning which takes place only in one direction. The purpose of this study was to determine the influence of PAI learning and Information Communication Technology-based ethics on student learning effectiveness at SMKN 14 Bandung. This study used a quantitative approach with a descriptive method. The data collection techniques used are Observation and Questionnaire. Data analysis techniques in the form of validity tests, reliability tests, parametic statistical prerequisite tests, hypothetical tests and t tests, and determination coefficient tests. The results of this study show that ICT-based PAI BP learning has a significant influence on student learning effectiveness. Based on the results of statistical testing using Spss in ICT-based PAIBP learning, tcalculate values= 2.153>2.0244, and Sig.0.001< 0.05 (5%), so Ho was rejected. This means that ICT-based PAIBP learning has a significant effect on student learning effectiveness.